2021
DOI: 10.1097/icl.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Endothelial Cell Changes After Femtosecond Laser–Assisted Cataract Surgery in Diabetic and Nondiabetic Patients

Abstract: To compare corneal endothelial cell changes after femtosecond laser-assisted cataract surgery (FLACS) in diabetic and nondiabetic patients. Methods: This retrospective study included patients with cataract who underwent FLACS performed by a single surgeon between August 2018 and November 2020. Changes in corneal endothelial cell density (ECD), hexagonality, coefficient of variation in cell size (CV), and central corneal thickness (CCT) at baseline and at the 1-month and 3-month postoperative follow-ups were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Femtosecond laser-assisted cataract surgery (FLACS) is reported to cause less damage to the corneal endothelium in patients with DM and can reduce the ECL. This may be because the corneal endothelial injury caused by the small energy during FLACS is insufficient to cause significant damage [ 44 ]. Therefore, FLACS may be a better option for patients with DM than conventional phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…Femtosecond laser-assisted cataract surgery (FLACS) is reported to cause less damage to the corneal endothelium in patients with DM and can reduce the ECL. This may be because the corneal endothelial injury caused by the small energy during FLACS is insufficient to cause significant damage [ 44 ]. Therefore, FLACS may be a better option for patients with DM than conventional phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…The femtosecond laser can accurately determine the diameter of the capsulorhexis, and create CCC, which can make a more centered and more circular opening, thereby avoiding the complications related to capsulorhexis to the greatest extent [51][52] . By segmenting the nucleus, femtosecond laser-assisted cataract surgery can reduce thermal or ultrasound energy and in turn protect the corneal endothelium [53] . Pajic et al [54] found that femtosecond laser-assisted cataract surgery could provide a reproducible capsulotomy and highly effective lens nucleus technology, which could bring good postoperative visual acuity and surgical safety.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, Cruz et al [ 28 ] demonstrated that in patients with diabetes and moderate cataracts, FLACS resulted in higher postoperative endothelial cell density when compared to CPCS at 3 months postoperatively, suggesting that there may be a protective role of FLACS in this group of patients as well. Likewise, Kang et al [ 29 ] also demonstrated that there was significantly thinner CCT in diabetics undergoing FLACS compared to CPCS.…”
Section: Endothelial Compromisementioning
confidence: 97%